Recovery, safety, and tolerability of a solvent/detergent‐treated and prion‐safeguarded transfusion plasma in a randomized, crossover, clinical trial in healthy volunteers. Issue 9 (16th January 2013) - Jilma‐Stohlawetz, Petra; Kursten, Friedrich W.; Horvath, Michaela; Leitner, Gerda; List, Jana; Marcek, Jana; Quehenberger, Peter; Schwameis, Michael; Bartko, Johann; Derhaschnig, Ulla; Jilma, Bernd
<x xml:space="preserve">Abstract</x> Background Octaplas LG is a prion‐depleted version of a previous generation product called Octaplas S/D. We compared the recovery, safety, and tolerability of these two pharmaceutical‐grade plasmas. Study Design and Methods In this comparative, block‐randomized, open‐label, active‐controlled, crossover Phase I trial, 60 healthy adult volunteers received single transfusions of 1200 mL of parent product (in Period 1) and of the LG plasma product (in Period 2) or vice versa. In both periods, plasmapheresis (600 mL) preceded the transfusion. Blood samples were drawn before and after apheresis and 15 minutes, 2 hours, 24 hours, and 7 days after end of plasma transfusion, to assess recovery, safety, and tolerability. The primary efficacy endpoints were the changes in coagulation factors and hemostatic variables compared to baseline; their relative recovery was computed in the per‐protocol analysis (n = 43). Safety and tolerability were assessed (n = 60). Results Variations in coagulation factors and hemostatic variables over time were similar between the two treatments and within normal range; 90% confidence intervals for the derived recovery data were within predefined limits of equivalence. Both products were well tolerated. The advanced manufacturing process also significantly increased plasmin inhibitor concentrations after transfusion in vivo. Conclusion The LG plasma product was bioequivalent to its predecessor with respect to recovery of clotting factors and demonstrated comparable safety and tolerability in healthy volunteers. Both products compensated well for the loss of clotting factors after apheresis (NCT01063595).